76.26.7 problem 7

Internal problem ID [17839]
Book : Differential equations. An introduction to modern methods and applications. James Brannan, William E. Boyce. Third edition. Wiley 2015
Section : Chapter 6. Systems of First Order Linear Equations. Section 6.4 (Nondefective Matrices with Complex Eigenvalues). Problems at page 419
Problem number : 7
Date solved : Tuesday, January 28, 2025 at 11:03:45 AM
CAS classification : system_of_ODEs

\begin{align*} \frac {d}{d t}x_{1} \left (t \right )&=x_{1} \left (t \right )+x_{2} \left (t \right )+x_{3} \left (t \right )\\ \frac {d}{d t}x_{2} \left (t \right )&=2 x_{1} \left (t \right )+x_{2} \left (t \right )-x_{3} \left (t \right )\\ \frac {d}{d t}x_{3} \left (t \right )&=-8 x_{1} \left (t \right )-5 x_{2} \left (t \right )-3 x_{3} \left (t \right ) \end{align*}

Solution by Maple

Time used: 0.007 (sec). Leaf size: 66

dsolve([diff(x__1(t),t)=1*x__1(t)+1*x__2(t)+1*x__3(t),diff(x__2(t),t)=2*x__1(t)+1*x__2(t)-1*x__3(t),diff(x__3(t),t)=-8*x__1(t)-5*x__2(t)-3*x__3(t)],singsol=all)
 
\begin{align*} x_{1} \left (t \right ) &= c_{2} {\mathrm e}^{-t}+c_{3} {\mathrm e}^{-2 t} \\ x_{2} \left (t \right ) &= c_{1} {\mathrm e}^{2 t}-\frac {4 c_{2} {\mathrm e}^{-t}}{3}-\frac {5 c_{3} {\mathrm e}^{-2 t}}{4} \\ x_{3} \left (t \right ) &= -\frac {2 c_{2} {\mathrm e}^{-t}}{3}-\frac {7 c_{3} {\mathrm e}^{-2 t}}{4}-c_{1} {\mathrm e}^{2 t} \\ \end{align*}

Solution by Mathematica

Time used: 0.005 (sec). Leaf size: 160

DSolve[{D[x1[t],t]==1*x1[t]+1*x2[t]+1*x3[t],D[x2[t],t]==2*x1[t]+1*x2[t]-1*x3[t],D[x3[t],t]==-8*x1[t]-5*x2[t]-3*x3[t]},{x1[t],x2[t],x3[t]},t,IncludeSingularSolutions -> True]
 
\begin{align*} \text {x1}(t)\to e^{-2 t} \left (c_1 \left (3 e^t-2\right )+(c_2+c_3) \left (e^t-1\right )\right ) \\ \text {x2}(t)\to \frac {1}{12} e^{-2 t} \left (6 c_1 \left (-8 e^t+3 e^{4 t}+5\right )+c_2 \left (-16 e^t+13 e^{4 t}+15\right )+c_3 \left (-16 e^t+e^{4 t}+15\right )\right ) \\ \text {x3}(t)\to \frac {1}{12} e^{-2 t} \left (-6 c_1 \left (4 e^t+3 e^{4 t}-7\right )+c_2 \left (-8 e^t-13 e^{4 t}+21\right )-c_3 \left (8 e^t+e^{4 t}-21\right )\right ) \\ \end{align*}